2014
DOI: 10.2399/jmu.2014002003
|View full text |Cite
|
Sign up to set email alerts
|

Complications of chronic otitis media: a retrospective analysis of 1293 cases

Abstract: Complications of chronic otitis media (COM) occur when the ear infection spreads to structures outside the middle ear mucosa, and the air spaces of the temporal bone. The spread of infection can occur via preformed pathways, bone Yöntem: Bu çal›flmada kronik otitis media tan›s› konulan 1293 hasta içerisinde komplikasyon saptanan 39 hastan›n klinik ve operatif bulgular› retrospektif olarak incelendi. Uygulanan cerrahi teknik, komplikasyonlar›n insidans› ve yönetimi, hastalar›n morbiditesi ve mortalitesi ilgili … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…[6,10,11] Open procedures are necessary when the disease has destroyed the posterior canal wall or in cases associated with intracranial complications. [12] The good hearing outcome is an air-bone gap between 0 and 20 dB for the three frequencies 0.5, 1 and 2 kHz. Tos and Lau found that 36% of patients with a CWDT had an air bone gap ≤20, and 50% of patients with an ICWT had an air bone gap ≤20 dB.…”
Section: Discussionmentioning
confidence: 97%
“…[6,10,11] Open procedures are necessary when the disease has destroyed the posterior canal wall or in cases associated with intracranial complications. [12] The good hearing outcome is an air-bone gap between 0 and 20 dB for the three frequencies 0.5, 1 and 2 kHz. Tos and Lau found that 36% of patients with a CWDT had an air bone gap ≤20, and 50% of patients with an ICWT had an air bone gap ≤20 dB.…”
Section: Discussionmentioning
confidence: 97%
“…Воспалительные заболевания центральной нервной системы, возникающие как осложнения острых или хронических очаговых процессов в ЛОР-органах, являются одной из важнейших проблем современной оториноларингологии и нейрохирургии [1][2][3][4][5][6]. Особенности клинической картины внутричерепных осложнений (ВЧО), характеризующихся преобладанием в клинической картине заболевания синдрома поражения головного мозга, тяжестью общего состояния больных, обусловливают трудности дифференциальной диагностики и лечения на всех этапах оказания медицинской помощи.…”
unclassified